IMPLEMENTATION STRATEGIC MANAGEMENT IN SMK PERGURUAN “CIKINI” JAKARTA - Tri HANDITO (Journal of Education and Leadership in Education, 2020)
This research aims to analyze the implementation of strategic management in SMK Perguruan “Cikini” Jakarta as an effort to improve the quality of schools. This research is a case study research. In this research, data obtained through observation, interviews with school leaders, and the person in charge of quality management, as well as work meeting documents and internal audit results. The results showed that SMK Perguruan “Cikini” has implemented four basic elements of strategic management. The various findings of non-compliance which are followed up with corrective actions indicate that SMK Perguruan “Cikini” able to respond to various problems found and make continuous improvements in maintaining school quality. The results of the internal audit and corrective actions are then used as feedback to develop a strategic plan the following year.